BIOPRO: UMPSA Researcher Dr. Nazrolnizah’s Biofeedback Protocol boosts performance of AIM Female Entrepreneurs - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 1 August 2025 – Many entrepreneurship programmes to date have focused heavily on business development strategies in both theory and practice but have often placed less emphasis on the internal growth of entrepreneurs, such as motivation, emotional resilience, and self-control.